Assessment of Inflammatory Markers in Children with Cow’s Milk Allergy Treated with a Milk-Free Diet - Ambroszkiewicz, Jadwiga (Nutrients, 2021)
Background: The aim of the study was to establish whether the use of a strict milk-free diet in children with cow’s milk allergy, resulting in the resolution of clinical symptoms of the disease, also extinguishes the inflammatory reaction induced by the allergy. Methods: We examined 64 children (aged 3–6 years) with a diagnosed cow’s milk allergy who had been treated with an elimination diet for at least six months and showed remission of the disease’s clinical symptoms as a result of the treatment. The control group consisted of 30 healthy children of the same age following an unrestricted age-appropriate diet. Concentrations of cytokines, calprotectin, and adipokines (leptin, resistin, chemerin, neutrophilic lipocalin associated with gelatinase—NGAL) were determined in the serum samples obtained from the studied children by immunoenzymatic assays. Results: Patients with CMA had significantly higher median values of serum IL-6, TNF-α, resistin, chemerin and NGAL in comparison to the healthy children (p < 0.05, p < 0.001, p < 0.05, p < 0.01, p < 0.001, respectively). Serum concentrations of IL-10, leptin, calprotectin and CRP as well as in WBC count were in the same range in both studied groups. We observed direct statistically significant correlations between levels of IL-10 and CRP (p = 0.005), IL-10 and WBC (p = 0.045), TNF-α and WBC (p = 0.038), calprotectin and WBC (p < 0.001), chemerin and CRP (p < 0.001) as well as between NGAL and WBC (p = 0.002) in children with CMA. Conclusion: The use of a strict milk-free diet by children with CMA, resulting in the resolution of clinical symptoms of the disease, does not seem to extinguish the inflammation induced by the allergy. The findings of this study—elevated IL-6, TNF-α, resistin, chemerin and NGAL levels in patients with CMA—suggest that these parameters seem to be involved in the generation of a low-grade proinflammatory environment observed in cow‘s milk allergy and could be used to monitor the effectiveness of treatment.